Improvement, Implementation, and Evaluation of the CMyLife Digital Care Platform: Participatory Action Research Approach - Lynn Verweij; Sanne J J P M Metsemakers; Geneviève I C G Ector; Peter Rademaker; Charlotte L Bekker; Bas van Vlijmen; Bert A van der Reijden; Nicole M A Blijlevens; Rosella P M G Hermens (JMIR Publications, 2023)
BackgroundThe evaluation of a continuously evolving eHealth tool in terms of improvement and implementation in daily practice is unclear. The CMyLife digital care platform provides patient-centered care by empowering patients with chronic myeloid leukemia, with a focus on making medication compliance insightful, discussable, and optimal, and achieving optimal control of the biomarker BCR-ABL1. ObjectiveThe aim of this study was to investigate to what extent the participatory action research approach is suitable for the improvement and scientific evaluation of eHealth innovations in daily clinical practice (measured by user experiences) combined with the promotion of patient empowerment. MethodsThe study used iterative cycles of planning, action, and reflection, whereby participants' experiences (patients, health care providers, the CMyLife team, and app suppliers) with the platform determined next actions. Co-design workshops were the foundation of this cyclic process. Moreover, patients filled in 2 sets of questionnaires for assessing experiences with CMyLife, the actual use of the platform, and the influence of the platform after 3 and at least 6 months. Data collected during the workshops were analyzed using content analysis, which is often used for making a practical guide to action. Descriptive statistics were used to characterize the study population in terms of information related to chronic myeloid leukemia and sociodemographics, and to describe experiences with the CMyLife digital care platform and the actual use of this platform. ResultsThe co-design workshops provided insights that contributed to the improvement, implementation, and evaluation of CMyLife and empowered patients with chronic myeloid leukemia (for example, simplification of language, and improvement of the user friendliness of functionalities). The results of the questionnaires indicated that (1) the platform improved information provision on chronic myeloid leukemia in 67% (33/49) of patients, (2) the use of the medication app improved medication compliance in 42% (16/38) of patients, (3) the use of the guideline app improved guideline adherence in 44% (11/25) of patients, and (4) the use of the platform caused patients to feel more empowered. ConclusionsA participatory action research approach is suited to scientifically evaluate digital care platforms in daily clinical practice in terms of improvement, implementation, and patient empowerment. Systematic iterative evaluation of users' needs and wishes is needed to keep care centered on patients and keep the innovation up-to-date and valuable for users.